Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1111/j.1365-4362.1996.tb03280.x
|View full text |Cite
|
Sign up to set email alerts
|

Double‐blind Study of Prednicarbate Versus Fluocortin Butyl Ester in Atopic Dermatitis

Abstract: Patients and Methods This parallel‐group, double‐blind trial compared the efficacy and tolerability of topical prednicarbate, 0.25% ointment, with that of fluocortin butyl ester, 0.75% ointment. The trial included 79 outpatients at three participating centers. All patients had a diagnosis of atopic dermatitis on the basis of Hanifin and Rajka's criteria.1 Other inclusion criteria were: age ≥ 18 years and stability or worsening of the condition for at least 1 week in the current episode. Patients were required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…PC induces potent anti-inflammatory effects in keratinocytes corresponding to BMV activity, which is well in accordance with clinical data [25,26]. The rapid metabolism of PC in keratinocytes [10] does not contradict a substance-specific antiphlogistic potency, as the RNAse protection assay proved native PC to be very active.…”
Section: Discussionsupporting
confidence: 63%
“…PC induces potent anti-inflammatory effects in keratinocytes corresponding to BMV activity, which is well in accordance with clinical data [25,26]. The rapid metabolism of PC in keratinocytes [10] does not contradict a substance-specific antiphlogistic potency, as the RNAse protection assay proved native PC to be very active.…”
Section: Discussionsupporting
confidence: 63%
“…The literature search yielded 602 titles of which 105 were included, and five additional studies were identified through hand searches 6,17,18,26–29,39,41–46,48–50,52,54–57,70,77,128–130,145–227 . Inclusion criteria included: trials reported as full length, English‐language papers, a length of treatment of 2 weeks or longer, and a sample size of 20 or more.…”
Section: Resultsmentioning
confidence: 99%
“…So far, most effective and consistent antipruritics remain systemic immunomodulators such as glucocorticoids, CyA, tacrolimus, pimecrolimus and ultraviolet radiation therapy (146, 241–244). Moreover, there are no evident and efficient alternatives to topical application of corticosteroids or calcineurin inhibitors for the control of acute episodes in AD (244–246). With reduction of skin lesions, a decreased itch intensity results probably because of reduction of inflammatory cells and protection of depolarization of nerve fibres mediated directly by the steroid (247).…”
Section: Management Of Pruritus In Allergic and Atopic Skin Diseasesmentioning
confidence: 99%